2016
DOI: 10.1007/s00384-016-2706-3
|View full text |Cite
|
Sign up to set email alerts
|

Liver test abnormalities predict complicated disease behaviour in patients with newly diagnosed Crohn’s disease

Abstract: BackgroundsIn coeliac disease, the prevalence of liver test abnormalities (LTAs) is higher in patients with more severe mucosal inflammation. In Crohn’s disease, prognosis is related to the severity of mucosal inflammation.AimThe aim of this study was to investigate whether the presence of LTA predicts the occurrence of complicated disease behaviour in newly diagnosed Crohn’s disease.MethodsA retrospective cohort study was performed in patients newly diagnosed with Crohn’s disease between 2002 and 2011. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…One patient with chronic liver disease (small duct PSC) was excluded. Of the 383 patients included in this study, 131 had liver test abnormalities (34.1%), but liver diseases were not found, apart from liver steatosis in 6% of patients [3] (versus 29% in the previous study [2]).…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…One patient with chronic liver disease (small duct PSC) was excluded. Of the 383 patients included in this study, 131 had liver test abnormalities (34.1%), but liver diseases were not found, apart from liver steatosis in 6% of patients [3] (versus 29% in the previous study [2]).…”
mentioning
confidence: 71%
“…In the more recent study [3], however, the authors found that, patients with liver test abnormalities, without an hepatic disease, more often developed complicated CD behaviour and more often needed hospitalization or surgery within 5 years of diagnosis than patients without liver test abnormalities. Patients with a C-reactive protein (CRP) <16 mg/L but with liver test abnormalities had a higher risk of developing complicated disease compared to those without liver test abnormalities.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Eosinophils are known to play an important role in the pathogenesis of asthma [29], with well-established genetic evidence indicating a protective effect of lower eosinophil count on asthma risk [30]. Liver test abnormalities are frequently observed in patients with inflammatory bowl diseases [31] and appear to be an risk factor for complications in patients with Crohn's disease [32]. Blood glucose has been observed to be elevated in patients experiencing chronic obstructive pulmonary disease (COPD) exacerbations [33].…”
Section: Application To Blood Traits and Immune Disorders In The Uk Biobankmentioning
confidence: 99%